Functional Properties of Gelatin Extracted from Skin of Sole fish (Cynoglossus macrostomus) (Norman, 1928) - Sawant, R. R.; Metar, S. Y.; Koli, J. M.; Nirmale, V. H.; Vishwasrao, V. V.; Temkar, G. S. (Fishery Technology, 2018)
Sole fish (Cynoglossus macrostomus, Norman, 1928) isa major by-catch of shrimp trawl and is a potentialsource of gelatin. Therefore a study on the extractionand determination of functional characteristics ofgelatin obtained from the skin of sole fish wasundertaken. Maximum yield obtained from skin ofsole fish was 8.32% at 45ºC. The proximatecomposition of extracted gelatin was found to becomparatively better at 45ºC. The gelatin extractedfrom the skin had high gel strength at 45ºC thanothers. Hydroxyproline content was found to be inthe range of 5.98-6.57 mg g-1 and highest content ofhydroxyproline was obtained at 45°C temperature.Sole fish skin gelatin was found to have lowermelting point than mammalian gelatin e.g. bovineand porcine gelatin. These promising finding maycontribute to the on-going efforts for using fishgelatin as an alternative source for mammaliangelatins for various applications.